Use of Simulation and Discussion Methods in Increasing Student Learning Motivation Madrasah Ibtidaiyah Teacher Education at STAI Kupang - Asliat Hingi Guhir (Journal of Indonesian Islamic Studies, 2023)
Being a teacher who is successful in learning is one process that is not easy to pass for a teacher. A learning is said to be successful if students succeed in learning, succeed in understanding what has been learned and are semanagat or motivated in following the learning process. Apart from all that, of course teachers must be creative in motivating students in various ways. One of them is creative in using the right methods in the teaching and learning process or learning process. The purpose of this study is to analyze the use of learning methods in motivating learning for PGMI STAI Kupang students in the even semester of 2021/2022. This type of research uses a qualitative approach. The data source amounted to 27 informants. Data collection techniques through observation and interviews. The data analysis technique uses trianggulation descriptions of sources. The results of research through interviews and observations prove that the use of simulation and discussion methods in learning activities can motivate the learning of Madrasah Ibtidaiyah Teacher Education (PGMI) students of STAI Kupang in the even semester of 2021/2022.